In Situ and Ex Situ Low‐Field NMR Spectroscopy and MRI Endowed by SABRE Hyperpolarization1. Issue 18 (3rd November 2014) - Barskiy, Danila A.; Kovtunov, Kirill V.; Koptyug, Igor V.; He, Ping; Groome, Kirsten A.; Best, Quinn A.; Shi, Fan; Goodson, Boyd M.; Shchepin, Roman V.; Truong, Milton L.; Coffey, Aaron M.; Waddell, Kevin W.; et al.
Abstract By using 5.75 and 47.5 mT nuclear magnetic resonance (NMR) spectroscopy, up to 105‐fold sensitivity enhancement through signal amplification by reversible exchange (SABRE) was enabled, and subsecond temporal resolution was used to monitor an exchange reaction that resulted in the buildup and decay of hyperpolarized species after parahydrogen bubbling. We demonstrated the high‐resolution low‐field proton magnetic resonance imaging (MRI) of pyridine in a 47.5 mT magnetic field endowed by SABRE. Molecular imaging (i.e. imaging of dilute hyperpolarized substances rather than the bulk medium) was conducted in two regimes: in situ real‐time MRI of the reaction mixture (in which pyridine was hyperpolarized), and ex situ MRI (in which hyperpolarization decays) of the liquid hyperpolarized product. Low‐field (milli‐Tesla range, e.g. 5.75 and 47.5 mT used in this study) parahydrogen‐enhanced NMR and MRI, which are free from the limitations of high‐field magnetic resonance (including susceptibility‐induced gradients of the static magnetic field at phase interfaces), potentially enables new imaging applications as well as differentiation of hyperpolarized chemical species on demand by exploiting spin manipulations with static and alternating magnetic fields.